Technology for the prevention of antimicrobial resistance and healthcare-associated infections; 2017 Geneva IPC-Think Tank (Part 2) - Zingg, Walter (Antimicrob Resist Infect Control, 2019)
BACKGROUND: The high burden of healthcare-associated infections (HAIs) and antimicrobial resistance (AMR) is partially due to excessive antimicrobial use both in human and animal medicine worldwide. How can technology help to overcome challenges in infection prevention and control (IPC) and to prevent HAI and emerging AMR? METHODS: In June 2017, 42 international experts convened in Geneva, Switzerland to discuss four potential domains of technology in IPC and AMR: 1) role and potential contribution of microbiome research; 2) whole genome sequencing; 3) effectiveness and benefit of antimicrobial environmental surfaces; and 4) future research in hand hygiene. RESULTS: Research on the microbiome could expand understanding of antimicrobial use and also the role of probiotics or even faecal transplantation for therapeutic purposes. Whole genome sequencing will provide new insights in modes of transmission of infectious diseases. Although it is a powerful tool for public health epidemiology, some challenges with interpretation and costs still need to be addressed. The effectiveness and cost-effectiveness of antimicrobially coated or treated environmental high-touch surfaces requires further research before they can be recommended for routine use. Hand hygiene implementation can be advanced, where technological enhancement of surveillance, technique and compliance are coupled with reminders for healthcare professionals. CONCLUSIONS: The four domains of technological innovation contribute to the prevention of HAI and AMR at different levels. Microbiome research may offer innovative concepts for future prevention, whole genome sequencing could detect new modes of transmission and become an additional tool for effective public health epidemiology, antimicrobial surfaces might help to decrease the environment as source of transmission but continue to raise more questions than answers, and technological innovation may have a role in improving surveillance approaches and supporting best practice in hand hygiene.